A protocol for a randomized comparison of extended-release versus sublingual buprenorphine among pre-trial detainees in jail - Rottapel, Rebecca E; Stopka, Thomas J; Friedmann, Peter D; Hoskinson Jr., Randall A; Englander, Daviana; Calhoun, Nicole; Senst, Thomas; Gudas, Christopher; Koutoujian, Peter J; Farabee, David (Tufts University Tisch Library, 2025)
Keywords: Extended-release buprenorphine, Jail, Corrections, Massachusetts, Medication for opioid use disorder, Pre-trial; Springer Open.